A Stearoyl–Coenzyme A Desaturase Inhibitor Prevents Multiple Parkinson Disease Phenotypes in α‐Synuclein Mice. Issue 1 (23rd October 2020) - Nuber, Silke; Nam, Alice Y.; Rajsombath, Molly M.; Cirka, Haley; Hronowski, Xiaoping; Wang, Junmin; Hodgetts, Kevin; Kalinichenko, Liubov S.; Müller, Christian P.; Lambrecht, Vera; Winkler, Jürgen; Weihofen, Andreas; et al.
Abstract : Objective: Parkinson disease (PD) has useful symptomatic treatments that do not slow the neurodegenerative process, and no significant disease‐modifying treatments are approved. A key therapeutic target in PD is α‐synuclein (αS), which is both genetically implicated and accumulates in Lewy bodies rich in vesicles and other lipid membranes. Reestablishing αS homeostasis is a central goal in PD. Based on previous lipidomic analyses, we conducted a mouse trial of a stearoyl–coenzyme A desaturase (SCD) inhibitor ("5b") that prevented αS‐positive vesicular inclusions and cytotoxicity in cultured human neurons. Methods: Oral dosing and brain activity of 5b were established in nontransgenic mice. 5b in drinking water was given to mice expressing wild‐type human αS (WT) or an amplified familial PD αS mutation (E35K + E46K + E61K ["3K"]) beginning near the onset of nigral and cortical neurodegeneration and the robust PD‐like motor syndrome in 3K. Motor phenotypes, brain cytopathology, and SCD‐related lipid changes were quantified in 5b‐ versus placebo‐treated mice. Outcomes were compared to effects of crossing 3K to SCD1 −/− mice. Results: 5b treatment reduced αS hyperphosphorylation in E46K‐expressing human neurons, in 3K neural cultures, and in both WT and 3K αS mice. 5b prevented subtle gait deficits in WT αS mice and the PD‐like resting tremor and progressive motor decline of 3K αS mice. 5b also increased αS tetramers and reduced proteinase K‐resistant lipid‐rich aggregates. Similar benefits accrued from genetically deleting 1 SCD allele, providing target validation. Interpretation: Prolonged reduction of brain SCD activity prevented PD‐like neuropathology in multiple PD models. Thus, an orally available SCD inhibitor potently ameliorates PD phenotypes, positioning this approach to treat human α‐synucleinopathies. ANN NEUROL 2021;89:74–90